2020
DOI: 10.3390/ijms21082987
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibitor Empagliflozin and DPP4 Inhibitor Linagliptin Reactivate Glomerular Autophagy in db/db Mice, a Model of Type 2 Diabetes

Abstract: Recent data have indicated the emerging role of glomerular autophagy in diabetic kidney disease. We aimed to assess the effect of the SGLT2 inhibitor empagliflozin, the DPP4 inhibitor linagliptin, and their combination, on glomerular autophagy in a model of type 2 diabetes. Eight-week-old male db/db mice were randomly assigned to treatment with empagliflozin, linagliptin, empagliflozin-linagliptin or vehicle for 8 weeks. Age-matched non-diabetic db/+ mice acted as controls. To estimate glomerular autophagy, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 70 publications
(110 reference statements)
6
58
0
Order By: Relevance
“…Thus, podocytes could be considered direct targets of SGLT2 inhibitors. We have shown recently that EMPA reactivated autophagic flux in the podocytes of db/db mice[ 46 ]; the promotion of autophagy could be an explanation of the renal protective effect of SGLT2 inhibitors[ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, podocytes could be considered direct targets of SGLT2 inhibitors. We have shown recently that EMPA reactivated autophagic flux in the podocytes of db/db mice[ 46 ]; the promotion of autophagy could be an explanation of the renal protective effect of SGLT2 inhibitors[ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…decreased sodium uptake by Na + /H + exchanger isoform 3 (NHE3) expression in proximal convoluted tubules (PTs) (128-133) reduced urinary excretion of angiotensin II and angiotensinogen levels in SGLT2 inhibitor-treated T2DM rats (134) did not further activate RAS in the long term, which prevented the RAS-mediated aggravation of cardiovascular and renal events (134,135) reduced urinary angiotensinogen excretion in patients with T2DM (136) increased urinary angiotensinogen excretion in patients with T1DM (137, 138) modulated the tubular expression of proteins governing the medullary concentration activity, further had an effect on fluid and electrolyte balance (139,140) (132) blocked the activation of the apoptotic-associated protein within PT cells (141) glomerular fibrosis or injury was not alleviated in SGLT2-knockout diabetic mice (142) modulated oxidative stress and intraglomerular inflammation and could thus alleviate renal fibrosis (143) alleviated the generation of vanin-1, the biomarker for oxidative stress within the kidney (144) lessened the epithelial-to-mesenchymal transition by modulating miR21 (145) alleviated renal fibrosis by lowering lipid accumulation-induced inflammation mediated by CD68 macrophages (146) activation of tubuloglomerular feedback: alleviated apoptosis by increasing autophagosomal formation within glomerular mesangial cells and podocytes (147,148) anti-inflammatory effects: decreased the levels of several cytokines such as tumor necrosis factora (TNFa), interleukin-6, high-sensitivity C-reactive protein, and leptin (149,150) restored oxygen supply, thereby alleviating the metabolic stress state in the mitochondria and restoring the hematocrit level in patients with DM (151,152) reduced ECM fibrosis by inflammation reduction and RAAS overactivation (153) the EPO-producing ability in patients with DM might be reversed after treatment with SGLT2i (154) suppressed HIF-1a-mediated metabolic switch from lipid oxidation to glycolysis in kidney tubule cells of diabetic mice.…”
Section: Mechanismsmentioning
confidence: 99%
“…SGLT2i also alleviates apoptosis by increasing autophagosomal formation within glomerular mesangial cells and podocytes. Korbut et al revealed that, in db/db mice, SGLT2i alone or with a DPP-4 inhibitor restored the glomerular autophagosomal formation [ 106 ]. Han et al also demonstrated that SGLT2i, along with thiazolidinedione, could alleviate the glomerular tuft area and mesangial expansion by reducing angiotensinogen and type 1 cytokine [ 107 ].…”
Section: Metabolic Factors Influenced By Sglt2imentioning
confidence: 99%